A comparative study of various screening tests of Asymptomatic Bacteriuria in pregnant women attending Antenatal Outpatient Department’ - Dr. Savitha B Hiremath; Dr. Renushree BV (Tropical Journal of Pathology and Microbiology, 2021)
Introduction: Urinary tract infections are the most common bacterial infections in pregnancy. Asymptomatic bacteriuria (ASB) refers to the presence of bacteria in the urine of an individual without symptoms of urinary tract infection. ASB which occurs in 2-11% of pregnancies is a major predisposition to the development of pyelonephritis.Aims and objectives: The aims and objectives of the study were to: Study the effectiveness of various screening tests: urine microscopy, gram stain, catalase test, leukocyte esterase test and nitrite test and to compare their sensitivity, specificity, positive predictive value and negative predictive value. Materials andMethods: The study included 500 pregnant women attending the outpatient department over 18 months. The urine samples collected in sterile containers were screened for urine microscopy, gram stain, catalase test, leukocyte esterase test and nitrite test. The samples were processed on CLED (Cysteine lactose electrolyte deficient) agar as the standard against which other screening tests are identified.Results: Gram’s stain (89.34%) was the most sensitive of all and the least reliable test was the catalase test among the methods of screening tests.Conclusion: Urine culture is considered to be the gold standard in detecting ASB in pregnant women. Gram’s stain of urine is a good screening test when compared to other screening methods. Screening for bacteria in all trimesters is necessary to prevent the dangerous complications associated with ASB.